2019
DOI: 10.1002/naaq.10096
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cecropin Transgenesis and Interspecific Hybridization on the Resistance to Ichthyophthirius multifiliis in Channel Catfish and Female Channel Catfish × Male Blue Catfish Hybrids

Abstract: The resistance of Channel Catfish Ictalurus punctatus, hybrid catfish (female Channel Catfish × male Blue Catfish I. furcatus [CB hybrids]), and Channel Catfish and hybrid catfish expressing the introduced cecropin B gene to Ichthyophthirius multifiliis infestation was investigated in two experiments. In experiment I, four fingerling groups were challenged, including cecropin‐transgenic Channel Catfish, cecropin‐transgenic CB hybrids, non‐transgenic Channel Catfish, and non‐transgenic CB hybrids. Non‐transgeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…The disease resistance against F. columnare and E. ictaluri of F 1 channel catfish possessing cecropin gene was increased by 27.3% and 14.8%, respectively, 162 and cecropintransgenic channel catfish conferred the similar resistance to Ich in hybrid catfish (channel catfish female x blue catfish male). 172 Sarmasik et al 163 applied the same construct into medaka, the result was in agreement with Dunham et al, 162 as the F 2 progeny of cecropintransgenic medaka acquired enhanced resistance to Pseudomonas fluorescens and Vibrio anguillarum infection. In addition, two cecropin constructs, porcine cecropin and one synthetic cecropin analog, were used to generate transgenic rainbow trout, exhibiting resistance against both bacteria (A. salmonicida) and virus (infectious haematopoietic necrosis virus).…”
Section: Transgenessupporting
confidence: 71%
See 1 more Smart Citation
“…The disease resistance against F. columnare and E. ictaluri of F 1 channel catfish possessing cecropin gene was increased by 27.3% and 14.8%, respectively, 162 and cecropintransgenic channel catfish conferred the similar resistance to Ich in hybrid catfish (channel catfish female x blue catfish male). 172 Sarmasik et al 163 applied the same construct into medaka, the result was in agreement with Dunham et al, 162 as the F 2 progeny of cecropintransgenic medaka acquired enhanced resistance to Pseudomonas fluorescens and Vibrio anguillarum infection. In addition, two cecropin constructs, porcine cecropin and one synthetic cecropin analog, were used to generate transgenic rainbow trout, exhibiting resistance against both bacteria (A. salmonicida) and virus (infectious haematopoietic necrosis virus).…”
Section: Transgenessupporting
confidence: 71%
“…The cecropin B gene, first discovered from the moth ( Hyalophora cecropia ), was the first exogenous AMG to be integrated into the genome of fish. The disease resistance against F. columnare and E. ictaluri of F 1 channel catfish possessing cecropin gene was increased by 27.3% and 14.8%, respectively, 162 and cecropin‐transgenic channel catfish conferred the similar resistance to Ich in hybrid catfish (channel catfish female x blue catfish male) 172 . Sarmasik et al 163 applied the same construct into medaka, the result was in agreement with Dunham et al, 162 as the F 2 progeny of cecropin‐transgenic medaka acquired enhanced resistance to Pseudomonas fluorescens and Vibrio anguillarum infection.…”
Section: Application Of Exogenous Amps/amgs In Fishmentioning
confidence: 98%
“…plans to expand the population to allow the testing of disease resistance. Cecropin transgenic Channel Catfish exhibited enhanced disease resistance compared to nontransgenic controls (Dunham et al 2002;Elaswad et al 2019). Based on the results of the current study, the cathelicidin transgenic approach should be more effective than the cecropin transgenic approach.…”
Section: Peptidementioning
confidence: 66%
“…2002; Elaswad et al. 2019). Based on the results of the current study, the cathelicidin transgenic approach should be more effective than the cecropin transgenic approach.…”
Section: Discussionmentioning
confidence: 99%
“…(Zhong et al, 2002;Chiou et al, 2014). However, Elaswad et al (2019) reported that there was a slight increase without significant differences in CSR of cecropintransgenic catfish compared to the wild-type group after the Ichthyophthirius multifiliis infection (55.75% vs 48.70%). Therefore, our meta-findings were supported by these individual studies.…”
Section: High Cumulative Survival Rates Denote Enhanced Resistance To...mentioning
confidence: 99%